2018
DOI: 10.1016/s0140-6736(17)33297-x
|View full text |Cite|
|
Sign up to set email alerts
|

Atezolizumab versus chemotherapy in patients with platinum-treated locally advanced or metastatic urothelial carcinoma (IMvigor211): a multicentre, open-label, phase 3 randomised controlled trial

Abstract: F Hoffmann-La Roche, Genentech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
1,036
10
32

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,208 publications
(1,110 citation statements)
references
References 30 publications
32
1,036
10
32
Order By: Relevance
“…The frequency of positive PD‐L1 assay outcome was lower than described in previous trials using the PD‐L1 (SP142) assay in advanced and metastatic bladder cancer, which reported a positive assay outcome in 25–32% . A possible explanation for this discrepancy might be the composition of study cohorts.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The frequency of positive PD‐L1 assay outcome was lower than described in previous trials using the PD‐L1 (SP142) assay in advanced and metastatic bladder cancer, which reported a positive assay outcome in 25–32% . A possible explanation for this discrepancy might be the composition of study cohorts.…”
Section: Discussioncontrasting
confidence: 58%
“…PD‐L1 expression was scored according to the manufacturer's guidelines . Briefly, PD‐L1 staining on immune cells was assessed in urothelial carcinoma areas occupied by tumour cells, associated intratumoral and contiguous peritumoral stroma.…”
Section: Methodsmentioning
confidence: 99%
“…Although this study was limited by phase II trial, atezolizumab received US-FDA approval for platinum-refractory mUC in May 2016 [202122]. In a recent multi-center, randomized phase III IMvigor211 clinical trial (NCT02302807), the clinical efficacy and safety of atezolizumab (1,200 mg intravenously, every three weeks) compared to chemotherapy (investigator's choice of vinflunine, paclitaxel, or docetaxel) were reported in 931 patients with mUC, whose disease had progressed despite platinum-based chemotherapy [23]. As a primary endpoint of the trial with atezolizumab, no significant improvement of OS was observed in the subset of 234 patients with ≥5% expression of PD-L1 on tumor-infiltrating ICs (median, 11.1 months vs. 10.6 months; hazard ratio [HR], 0.87; 95% confidence interval [CI], 0.63–1.21); ORR was similar (23% vs. 22%).…”
Section: Immune Checkpoint Inhibitors After Platinum-based Chemotheramentioning
confidence: 99%
“…Based on these results, atezolizumab received accelerated approval as a first‐line treatment for cisplatin‐ineligible patients with locally advanced or mUC. However, the result of a randomized, open‐label, phase III trial (IMvigor211; n = 931) showed that atezolizumab use in platinum‐refractory mUC patients ( n = 234 [25%]) with ≥5% expression of PD‐LI on tumor infiltrating immune cells did not show statistically significant benefits in OS as compared with the OS benefits after chemotherapy . Grade ≥3 adverse events occurred in 20% with atezolizumab and in 43% with chemotherapy.…”
Section: Immunotherapy In Ucmentioning
confidence: 99%